2012
DOI: 10.1128/iai.06214-11
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role ofd-Amino Acid Oxidase against Staphylococcus aureus Infection

Abstract: ABSTRACTd-Amino acid oxidase (DAO) is a hydrogen peroxide-generating enzyme that uses ad-amino acid as a substrate. We hypothesized that DAO may protect against bacterial infection, because hydrogen peroxide is one of the most important molecules in the antibacterial defense systems in mammals. We show here that DAO suppressed the growth of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…168,169 A later study showed that DAO is localized in the neutrophilic surface, internalized during phagocytosis, and is capable of H 2 O 2 production within the phagosome. 170 Mice lacking DAO activity were shown to be more susceptible to intravenous injection with Staphylococcus aureus, 171 supporting a role for neutrophilic DAO in systemic innate defense that is responsive to microbial input. More recently, microbial d-amino acids also have been associated with the immune system in the mucosa.…”
Section: D-amino Acids From Commensal and Pathogenic Bacteria In Mammalsmentioning
confidence: 98%
“…168,169 A later study showed that DAO is localized in the neutrophilic surface, internalized during phagocytosis, and is capable of H 2 O 2 production within the phagosome. 170 Mice lacking DAO activity were shown to be more susceptible to intravenous injection with Staphylococcus aureus, 171 supporting a role for neutrophilic DAO in systemic innate defense that is responsive to microbial input. More recently, microbial d-amino acids also have been associated with the immune system in the mucosa.…”
Section: D-amino Acids From Commensal and Pathogenic Bacteria In Mammalsmentioning
confidence: 98%
“…Previous studies have suggested that DAO may contribute to systemic defense against pathogens via the activity of neutrophil DAO 18,19 . To test whether DAO activity is important to mucosal defense in vivo, we explored the effect of DAO and D-aa on V. cholerae intestinal colonization in streptomycin-treated adult mice.…”
mentioning
confidence: 99%
“…This paradoxical observation needs clarification, since both enzymes are capable of decomposing H 2 O 2 , but the physiological effect of their combined action is antipodal. Nevertheless, it is reliably known that an increase in the D-serine level and a decrease in DAAO activity are efficient in treating various diseases, including mental disorders and oncological ones [40][41][42][43][44][45].…”
Section: Abstract: D-amino Acids D-amino Acid Oxidase Peroxisomes mentioning
confidence: 99%